Meningiomas in Childhood - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The clinical presentation and pathological characteristics of 18 meningiomas among 240 surgically verified intracranial space-occupying lesions in children are reported from the Depts of Neurosurgery and Pathology, National Inst of Mental Health, Bangalore and Nizam's Inst of Med Sciences, Panjagutta, Hyderabad, India.